1972
DOI: 10.1007/bf00191112
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic fracture models and structural reliability

Abstract: A kinetic model is postulated which considers the interaction of cumulative fatigue damage and chance overload on a component or structure under typical probabilistic service load histories. This model recognizes that:[I] materials fail from pre-existing flaws; [2] that flaws develop in a characteristic manner which is determined by the material properties, state and magnitude of the stresses at the flaw perimeter, the history of the imposed tractions, the thermal and environmental histories; and [3] the criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Experimental fatigue data [6] for unnotched composite laminates under constant amplitude cyclic stress show that the residual strength after n cycles decreases monotonically with n . Halpin et al [7] assumed that the rate of degradation in the residual strength is inversely proportional to a power function of residual strength.…”
Section: Residual Strength Degradation Equationmentioning
confidence: 93%
See 2 more Smart Citations
“…Experimental fatigue data [6] for unnotched composite laminates under constant amplitude cyclic stress show that the residual strength after n cycles decreases monotonically with n . Halpin et al [7] assumed that the rate of degradation in the residual strength is inversely proportional to a power function of residual strength.…”
Section: Residual Strength Degradation Equationmentioning
confidence: 93%
“…Initially, Broutman and Sahu [1] proposed a simple linear degradation model for determining the residual strength of composites. Later, Halpin et al [6,7] assumed that the residual strength is a monotonically decreasing function of the number of fatigue cycles. Its rate of degradation is the product of a power function of residual strength and a function of maximum cyclic stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halpin et al [10] fi rst showed that for unnotched composite laminates under constant-amplitude cyclic stress, the residual strength Z ( n ) after n cycles decreases monotonically with n . Halpin et al [11] also assumed that the slope of residual strength can be approximated by dividing a function of the maximum cyclic stress by a power function of Z ( n ).…”
Section: Strength Degradation Equationmentioning
confidence: 98%
“…The fatigue failure is assumed to occur when the residual strength R(n) has been reduced to the value of the maximum cyclic stress amax, i.e., when Substitution of Equation 9 into Equation 8 results in an expression for the fatigue life, N, in the form The ultimate strength R(0) is a statistical variable assumed to follow the twoparameter Weibull distribution [References 1, 3-13] , in which FR (0) (x) is the distribution function denoting the probability that the ultimate strength R(0) is smaller than a value x. In Equation 11, a and j3 are the shape parameter and the scale parameter (or characteristic strength), respectively.…”
Section: Statistical Distribution Of Fatigue Life and Residual Strengthmentioning
confidence: 99%